Evaluation of seismic energy demand. - Manfredi, Gaetano
In this paper, a method is proposed in order to obtain a simplified representation of hysteretic and input energy spectra. The method is based on the evaluation of the equivalent number of cycles correlated to the earthquake characteristics by the proposed seismic index ID. This procedure allows us to obtain peak values of the hysteretic and input energy that depend on the demanded ductility, on the seismic index ID and on the peak pseudo-velocity. The assessment of the input energy represents a first step towards the definition of a damage potential index capable of taking into account the effect of the duration of the ground motions.
Keywords: Input energy; Hysteretic energy; Damage potential